IMPLEMENTATION OF DIGITAL POPULATION IDENTITY (IKD) AT THE POPULATION AND CIVIL REGISTRATION SERVICE OF EAST BOLAANG MONGONDOW REGENCY - Sri Herlina Mokodompit; Sisca B. Kairupan; Devie S. R. Siwij (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the implementation of Digital Population Identity (IKD) at the Department of Population and Civil Registration of East Bolaang Mongondow Regency. This research employs a qualitative method with a descriptive approach. Data collection techniques were conducted through interviews, observations, and documentation. The analysis uses Edward III's policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the implementation of the IKD program at the Department of Population and Civil Registration of East Bolaang Mongondow Regency has been running fairly well. However, several obstacles remain, such as low levels of digital literacy among the community, limited technological devices, insufficient socialization program to the public, and internet network constraints. Therefore, it is necessary to enhance program socialization, strengthen technological infrastructure support, and improve community digital literacy so that the implementation of the IKD program can run more optimally in improving the quality of population administration services in East Bolaang Mongondow Regency.